The effect of COVID-19 and CEO tenure on environmental and social disclosure scores - Teja, Adrian (Journal of Accounting and Investment, 2024)
Research aims: The study aims to understand the effect of COVID-19 and the tenure of Chief Executive Officers (CEOs) on environmental and social disclosure scores.Design/Methodology/Approach: The research sample included listed Indonesian firms, excluding those in the financial sector, for 2015-2021. The samples were analyzed by cross-sectional data regression and controlled by corporate governance mechanisms proxied by the number of women and independent Boards of Commissioners, leverage, size, profitability, and growth opportunity proxied by price-to-book-value ratio and capital-expenditure-to-depreciation ratio.Research Findings: The COVID-19 pandemic has positively affected environmental and social disclosure scores. While CEO tenure negatively affected social disclosure scores, its effect on environmental disclosure scores was statistically insignificant.Theoretical Contribution/Originality: The study provides empirical evidence on the progression of change in environmental and social disclosure scores triggered by COVID-19.Practitioner/Policy Implications: CEOs need to be persuaded and incentivized to increase their firms’ commitment to enhancing social performance and disclosure scores after COVID-19.Research Limitation/Implications: The effect of the COVID-19 pandemic and CEO tenure on environmental and social disclosure scores from firms with high stock market capitalization were analyzed. The data did not yet consider the medium and small stock market capitalization firms.